Current Insights into the Effectiveness of Riparian Management, Attainment of Multiple Benefits, and Potential Technical Enhancements. Issue 2 (1st March 2019) - Stutter, Marc; Kronvang, Brian; Ó hUallacháin, Daire; Rozemeijer, Joachim
Abstract : Buffer strips between land and waters are widely applied measures in diffuse pollution management, with desired outcomes across other factors. There remains a need for evidence of pollution mitigation and wider habitat and societal benefits across scales. This paper synthesizes a collection of 16 new primary studies and review papers to provide the latest insights into riparian management. We focus on the following areas: (i) diffuse pollution removal efficiency of conventional and saturated buffer strips, (ii) enhancing biodiversity of buffers, (iii) edge‐of‐field technologies for improving nutrient retention, and (iv) potential reuse of nutrients and biomass from buffers. Although some topics represent emerging areas, for other well‐studied topics (e.g., diffuse pollution), it remains that effectiveness of conventional vegetated buffer strips for water quality improvement varies. The collective findings highlight the merits of targeted, designed buffers that support multiple benefits, more efficiently interrupting surface and subsurface contaminant flows while enhancing diversity in surface topography, soil moisture and C, vegetation, and habitat. This synthesis also highlights that despite the significant number of studies on the functioning of riparian buffers, research gaps remain, particularly in relation to (i) the capture and retention of soluble P and N in subsurface flows through buffers, (ii) the utilization of captured nutrients, (iii) the impact of buffer design and management on terrestrial and aquatic habitats and species, and (iv) the effect of buffers (saturated) on greenhouse gas emissions and the potential for pollution swapping. Core Ideas: We present an updated synthesis on riparian management incorporating insights from 16 new papers. Topics cover diffuse pollution, biodiversity, new technologies, and biomass reuse. The synthesis shows a move toward designed elements to improve riparian functions.